Response of mouse thymic cells to radiation after transfusion of mesenchymal stem cells. Issue 51 (December 2016) - Zhang, Hongmei; Wang, Ling; Guo, Chunlong; Tong, Zhimin; Liu, Yue; Meng, Xiangkuan; Feng, Hu; Chen, Yubing
Abstract : Abstract: Thymic lymphoma is a highly invasive and even metastatic cancer. This study investigated the effects of mesenchymal stem cells (MSCs) transfusion on cell cycle, cell proliferation, CD3 expression, mutation frequency of T cell receptor using mouse model of thymic lymphoma. C57BL/6J young mouse models of thymoma were injected with MSCs. Six months later, the thymus was taken for pathological examination and flow cytometry studies. The cells were labeled with anti-CD4, CD8, CD3, propidium iodide, or CFDA-SE, cell cycle, proliferation kinetics, and mutation frequency of T cell receptor, respectively. Pathologic results showed that control had clear corticomedular structure with regularly shaped lymphocytes. After radiation, the thymus structure was completely destroyed, with lymphoid tumor cells diffusely distributed and heavily stained, and large nuclei. Transfusion of MSCs resulted in normal thymus structure. Cytometry studies showed that there were more CD4-/CD8- T cells in the thymus of irradiated mice than in control; transfusion of MSCs led to reduced CD4-/CD8- T cells. In irradiated mice, there were less CD4+/CD8+ T cells than in control and MSCs transfusion groups. It was observed that there were more cells arrested in G1 phase in the thymus cells and CD4-/CD8- T cells in irradiated mice than in other 2 groups, whereas there were more cells arrested in S phase in CD4+/CD8+ and CD4+/CD8- T cells in irradiated mice than in the other mice. In the thymus cells, and CD4+/CD8+ and CD4+/CD8- T cells, irradiated mice group had significantly less parent, G2, G3, and G4 cells, and more cells at higher generations, and also higher proliferation index. In CD4-/CD8- T cells, irradiated mice had significantly more parent, G2, and G3 cells, and less G4, G5, G6, and propidium iodide, as compared with the other 2 groups. The expression of CD3 in CD4/CD8 T cells was significantly higher than in control. MSCs transfusion improved CD3 expression, but was still less than the control. Irradiation resulted in very high mutation frequency of T cell receptor, which was barely affected by MSCs transfusion. Mesenchymal stem cell transfusion is able to restore the cell cycle and cell proliferation, but not CD3 expression and mutation frequency of T cell receptor in irradiated mice to control level.